Respuesta a Joshua Cohen - Pogge, Thomas (2011)
In this article, Thomas Pogge anwers to the critics of Joshua Cohen. In this\norder, he inquiries what is the appropriate standard of proof for evaluating the Strong\nThesis, he presents and examines specific reform proposals of the global order ?such\nas the elimination of protectionist barriers from rich countries, the modification of global\nrules governing resource extraction and the creation of a Health Impact Fund?, and\nhe analyses the impact that this reforms could have on global poverty and inequality